Etiology of anxious and fearful behavior in juvenile neuronal ceroid lipofuscinosis (CLN3 disease) - Ostergaard, John R. (Frontiers in Psychiatry, 2023)
Abstract: Background: Juvenile neuronal ceroid lipofuscinosis (JNCL, CLN3) is a childhood-onset neurodegenerative disease with prominent symptoms comprising a pediatric dementia syndrome. As in adult dementia, behavioral symptoms like mood disturbances and anxiety are common. In contrast to in adult dementia, however, the anxious behavioral symptoms increase during the terminal phase of JNCL disease. In the present study, the current understanding of the neurobiological mechanisms of anxiety and anxious behavior in general is addressed as will a discussion of the mechanism of the anxious behavior seen in young JNCL patients. Based on developmental behavioral points of view, known neurobiological mechanisms, and the clinical presentation of the anxious behavior, a theory of its etiology is described. Result and discussion: During the terminal phase, the cognitive developmental age of JNCL patients is below 2 years. At this stage of mental development individuals act primarily from a concrete world of consciousness and do not have the cognitive ability to encounter a normal anxiety response. Instead, they experience the evolutionary basic emotion of fear, and as the episodes typically are provoked when the adolescent JNCL patient is exposed to either loud sounds, is lifted from the ground, or separated from the mother/known caregiver, the fear can best be perceived as the developmental natural fear-response that appears in children 0-2 years of age. The efferent pathways of the neural fear circuits are mediated through autonomic, neuroendocrine, and skeletal-motor responses. The autonomic activation occurs early, is mediated through the sympathetic and parasympathetic neural systems, and as JNCL patients beyond puberty have an autonomic imbalance with a significant sympathetic hyperactivity, the activation of the autonomic nervous system results in a disproportionate high sympathetic activity resulting in tachycardia, tachypnea, excessive sweating, hyperthermia, and an increased atypical muscle activity. The episodes are thus phenotypically similar to what is seen as Paroxysmal Sympathetic Hyperactivity (PSH) following an acute traumatic brain injury. As in PSH, treatment is difficult and so far, no consensus of a treatment algorithm exists. Use of sedative and analgesic medication and minimizing or avoiding provocative stimuli may partly reduce the frequency and intensity of the attacks.